2007
DOI: 10.1164/rccm.200602-270oc
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Risk Factors for Vascular Disease in Obstructive Sleep Apnea

Abstract: In a sleep clinic population, men with OSA and no identifiable cardiovascular disease have increased insulin resistance and other metabolic changes that act to increase the risk of vascular disease, compared with age- and body mass index-matched attendees without OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(164 citation statements)
references
References 27 publications
8
142
2
11
Order By: Relevance
“…Contrary to such an expectation, we found significant increases in SC fat and WC and very small increases in TBF, while TBM remained almost constant over the 8 months of ventilation. It is currently unclear if such changes impact upon the metabolic burden of OSAS patients, since several alterations associated with this disease are independent of fat tissues (12,39). Apparently, the effects of CPAP on BC in OSAS are distinct from the effects of GH in GHD, where TBF is usually decreased, in addition to an increase in IGF1 and LBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to such an expectation, we found significant increases in SC fat and WC and very small increases in TBF, while TBM remained almost constant over the 8 months of ventilation. It is currently unclear if such changes impact upon the metabolic burden of OSAS patients, since several alterations associated with this disease are independent of fat tissues (12,39). Apparently, the effects of CPAP on BC in OSAS are distinct from the effects of GH in GHD, where TBF is usually decreased, in addition to an increase in IGF1 and LBM.…”
Section: Discussionmentioning
confidence: 99%
“…The physiologic release of GH in healthy humans is stimulated by GHRH as a function of sleep depth (9). Thus, continuous positive airway pressure (CPAP) therapy may lead to a restoration of the GH axis activity to a more physiological pattern, and consecutively affect BC (6,(10)(11)(12). Adipose tissue has been associated with most of the metabolic burden associated with OSAS (7,13,14), and short-term CPAP reduces V fat (15).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a more recent study, 27 reported that leptin was significantly higher in 21 OSA patients, compared to 21 healthy subjects matched for age and BMI, but this was not retained in multiple regression analysis which accounted for BMI. Three previous studies have investigated the relation between OSA and ghrelin.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 94%
“…Obesity and sleep apnea are often associated with dysregulation of glucose and lipid metabolism (121)(122)(123)(124)(125), although the precise mechanisms for these associations are not well understood. In recent years, investigators have examined metabolic responses to excess caloric intake and have identified specific signaling factors responsible for disturbances in metabolic and upper airway control.…”
Section: Putative Adipokine Modulators Of Upper Airway Functionmentioning
confidence: 99%